Optimising Absorption in Luminescent Solar Concentrators constraint by Average Visible Transmission and Color Rendering Index - de Bruin, Thomas A.; van Sark, Wilfried G. J. H. M. (Frontiers in Physics, 2022)
The luminescent solar concentrator (LSC) as energy harvesting window is an emerging technology in the realm of building integrated photovoltaics. Using recent advancement for assessing the balance between transmitted color quality and potential electricity generation, this paper optimizes theoretical luminophore absorption spectra for the highest power generation possible. The power conversion efficiencies (PCE) are based on coupling of the LSC waveguide to a highly efficient crystalline silicon solar cell. A non-convex optimisation algorithm maximizing absorption is used with constraints for color quality parameters: average visible transmission (AVT) and color rendering index (CRI). An optimal luminophore has been defined using a continuous absorption function with a cut-off and limited absorption in the visible spectrum. Two types of constraints are set: 1) 55% < AV T < 100% and 2) 55% < AV T < 100% and 70 < CRI < 100. The first constraint will ensure sufficient visible light and the second ensures appropriate color rendering. Ray-trace validated results show high power conversion efficiencies ranging from 10.0% - 15.1% for [AVT = 90%, CRI = 98] and [AVT = 55%], respectively. Future studies can use these results to define maximum absorption possibilities based on specific lighting requirements. Furthermore, the flexibility of the proposed method allows for the adaptation to constraints not used in this paper.